Migration strategy and pathogen risk: non-breeding distribution drives malaria prevalence in migratory waders - Clark, N; Clegg, S; Klaassen, M (Nordic Ecological Society, 2016)
Pathogen exposure has been suggested as one of the factors shaping the myriad of migration strategies observed in nature. Two hypotheses relate migration strategies to pathogen infection: the “avoiding the tropics hypothesis” predicts that pathogen prevalence and transmission increase with decreasing non-breeding (wintering) latitude, while the “habitat selection hypothesis” predicts lower pathogen prevalence in marine than in freshwater habitats. We tested these scarcely investigated hypotheses by screening wintering and resident wading shorebirds (Charadriiformes) for avian malaria blood parasites (Plasmodium and Haemoproteus spp.) along a latitudinal gradient in Australia. We sequenced infections to determine if wintering migrants share malaria parasites with local shorebird residents, and we combined prevalence results with published data in a global comparative analysis. Avian malaria prevalence in Australian waders was 3.56% and some parasite lineages were shared between wintering migrants and residents, suggesting active transmission at wintering sites. In the global dataset, avian malaria prevalence was highest during winter and increased with decreasing wintering latitude, after controlling for phylogeny. The latitudinal gradient was stronger for waders that use marine and freshwater habitats (marine+freshwater) than for marine-restricted species. Marine+freshwater wader species also showed higher overall avian malaria parasite prevalence than marine-restricted species. By combining datasets in a global comparative analysis, we provide empirical evidence that migratory waders avoiding the tropics during the non-breeding season experience a decreased risk of malaria parasite infection. We also find global support for the hypothesis that marine-restricted shorebirds experience lower parasite pressures than shorebirds that also use freshwater habitats. Our study indicates that pathogen transmission may be an important driver of site selection for non-breeding migrants, a finding that contributes new knowledge to our understanding of how migration strategies evolve.